Forum: How Heterodox is the Mainstream? Economic Theory and Economic Policy Advice in the English-speaking Area. Survey by the journal Intervention. - Torsten Niechoj (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2007)
Erster Absatz: At the beginning of December 2006, INTERVENTION asked its Scientific Board and the authors of previous issues for their views on the relationship of heterodox economic theory to the mainstream of economics. We asked those who are living and working in the English-speaking area to relate their assessment to this area. Board members and authors in German-speaking countries were requested to assess the situation there. The submitted answers are printed below starting with the contributions concerning the English-speaking area (in English) and followed by the contributions concerning the German-speaking area (in German) on page 12.
Keywords: 330